O estruturalismo em livros didáticos: SMSG e matemática - curso moderno - Correia, Carlos Eduardo Félix [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The goal of this research was to analyze how the structuralism has been present in the mathematics teachings proposal of two works for the Brazilian high school between the years of 1960 and 1970, being: the book 1 of the collection SMSG -School Mathematics Study Group - Mathematics for Junior High School Course and the book 1 of the work of Professor Osvaldo Sangiorgi Mathematics- Modern Course for Junior High School. Both began to diffuse in Brazil from 1964. We have taken by methodological referential the hermeneutics of profundity proposed by Thompson (1995) in three dimensions of analysis: Social-Historic analysis, formal analysis or discursive analysis and the interpretation-reinterpretation. We agree with Oliveira (2008) that the didactics books can be considered as Symbolic Forms and, thus, are passive of several interpretations. We have concluded that the structuralism has been present in the two analyzed works. In the book of SMSG, under the light of logic, by the method of reasoning to the construction of the mathematics concepts, in this, the students are led to a way of structuring the reason the think the mathematics by the logical principle of deduction. In the book of Sangiorgi, under the light of formalism, approaching the ideas proposed by Bourbaki, in his work Elements of mathematics which demonstrate the concern with the axiomatic exposition that proceeds from the general to the private in a depurated presentation, a profound unit that lies on the Theory of Sets and hierarchical in terms of abstract structures. The authors concerns with the conceptual pre-requisites, obeying the phase of the construction of the mathematical knowledge and observing, above all, values, attitudes, anxieties, abilities and motivation, attests also the presence of the psychological structuralism of Piaget in both works

O objetivo desta pesquisa foi analisar como que o estruturalismo esteve presente nas propostas do ensino de Matemática de duas obras para os Ginásios brasileiro entre os anos de 1960 e 1970, quais sejam: o Volume 1 da coleção SMSG - School Mathematics Study Group - Matemática - Curso Ginasial e o Volume 1 da obra do Professor Osvaldo Sangiorgi Matemática - Curso Moderno para os Ginásios. Ambas começaram a circular no Brasil a partir de 1964. Tomamos por referencial metodológico a Hermenêutica de Profundidade proposto por Thompson (1995) em três dimensões de análise: análise sócio-histórica, análise formal ou discursiva e a interpretação/reinterpretação. Concordamos com Oliveira (2008) que os livros didáticos podem ser considerados como formas simbólicas e, portanto, são passíveis de diversas interpretações. Concluímos que o estruturalismo esteve presente nas duas obras analisadas. No livro do SMSG à luz do logicismo, pelo método de raciocínio para a construção dos conceitos matemáticos, neste os estudantes são conduzidos a um modo de estruturar o raciocínio para pensar a Matemática pelo princípio lógico da dedução. No livro de Sangiorgi à luz do formalismo, aproximando-se das ideias propostas por Bourbaki em sua obra Elementos de Matemática, as quais demonstravam a preocupação com o modo de exposição axiomático, que se procede do geral para o particular em uma apresentação depurada, uma profunda unidade que repousa sobre a Teoria dos Conjuntos e hierarquizada em termos de estruturas abstratas. A preocupação dos autores com os pré-requisitos conceituais, obedecendo às etapas da construção do conhecimento matemático e observando, sobretudo, valores, atitudes, ansiedades, habilidades e motivação, atesta também a presença do estruturalismo psicológico de Piaget nas duas obras
Keywords: Sangiorgi, Osvaldo 1921; Movimento Matemática Moderna; Matemática - Estudo e ensino; Matemática - História - 1960-1970; Material didático; Mathematics - Study and teaching